Panorama do PRONAF nas mesorregiões do Rio Grande do Sul: análise no período de 2005 a 2015 - Silveira, Felipe Lopes da (2019)
This paper aimed to analyze the impact of the National Program for Strengthening Family Farming (PRONAF) in Rio Grande do Sul state, from the perspective of its mesorregions. To do so, it was evaluated whether resources from PRONAF contribute to the improvement of FIRJAN Index of City Development (IFDM), wheter these reseources impact on the poverty reduction through the number of families written in the Unified Registry for Social Programs (CadÚnico) and whether they have been directed to the poorer regions of the state when related to the municipal Gross Product and the the Regional Credit Index. The data were obtained, segmented by municipalities, from the Brazilian Institute of Geographic Statistics (IBGE) – population, the municipal gross product per capita, the agricultural gross product per capita, from the Federation of Industries of the State of Rio de Janeiro (FIRJAN) – IFDM, from the Ministry of Social Development – number of families registered in CadÚnico – and from the Central Bank of Brazil (BACEN) – monetary values of the program financing. These data comprised the period from 2005 to 2015. For the data analysis, it was used descriptive statistics techniques to describe the evolution of PRONAF credit and development indicators, mean difference tests for analysis of differences according to mesorregions and panel data analysis by the Driscoll-Kraay technique in order to estimate the program impact on indicators. The results showed that, in most municipalities, the credit is larger than their gross products and agricultural gross products and that the most assisted mesorregion is the northwestern one and the least assisted is the metropolitan one. They also demonstrated that PRONAF reaches the poorest municipalities, contributes to the IFDM improvement and the poverty reduction, although mildly.